A landscape of preservation: late prehistoric settlement and sequence in the Jebel Qurma region, north-eastern Jordan. (August 2014) - Akkermans, Peter M. M. G.; Huigens, Harmen O.; Brüning, Merel L.
<x content-type="archive" xml:space="preserve">Abstract</x> Recent fieldwork in the Jebel Qurma region, in the basalt wasteland east of Azraq, revealed a large number of prehistoric sites, dating from the 7th to the late 4th millennia cal bc. While some sites were little more than lithic scatters over a few dozen square metres, others were of impressive size, up to 8 hectares in extent and characterized by hundreds of stone-built structures. The new data demonstrate considerable diversity in site layout as well as clear shifts in habitation patterns and locational preferences through time. These new insights require a re-evaluation of current thoughts on settlement and community organization in the basaltic uplands of north-eastern Jordan in the Neolithic and Chalcolithic periods.